Monitoring strategies for the Citrus Mealybug in Citrus orchards (Bollettino di zoologia agraria e bachicoltura, 2024)
The Citrus Mealybug (CM), Planococcus citri (Risso), is a major pest in many citrus growing areas. Sampling of CM prior to fruit colonisation in the spring is difficult and presents an obstacle to CM management. Monitoring population densities is based on male capture using traps baited with female sex pheromone. In an attempt to establish the basis for a reliable monitoring of CM population, the correlation between male captures by pheromone traps and fruit infestation levels was investigated in the citrus orchards of Portugal, Israel and ltaly simultaneously. No significant linear relationship was found between male captures and fruit infestation at subplot level in ali three countries, which suggests that the range of attraction of each pheromone trap extend further than the distance between the trap and neighbouring trees sampled for estimation of mealybug density. lt is likely that the high flight activity and high mobility of the males render irrelevant the contribution of the male population to the total amount of male capture inside the subplots. At the orchard level, the diverse population density between plots allowed significant linear relationship in certain trapping periods between male capture and fruit infestation. Information on the level of male capture in spring or early summer by application of pheromone traps may be used to predict mealybug density or percentage of fruit infestation and consequently to assist in the decision making for the purpose of CM management.
Keywords: Planococcus citri; pheromone traps; decision tools